Population genetic structure and dispersal patterns of a cooperative breeding bird in variable environmental conditions. (January 2022) - Leon, Constanza; Banks, Sam; Beck, Nadeena; Heinsohn, Robert
Abstract : Understanding the effects of environmental conditions in cooperatively breeding species helps reveal the nature of evolutionary forces leading to this type of social system. In particular, environmental variability may affect demographic processes such as mortality and dispersal which can ultimately define the fine-scale genetic structure of cooperatively breeding populations, including direct and indirect fitness opportunities for individuals. We investigated the population genetic structure and dispersal patterns of obligately cooperative white-winged choughs, Corcorax melanorhamphos, exploring within-group relatedness and genetic differentiation among groups sampled over several years of above average rainfall. We compared our results with data from a previous study in the surrounding area, conducted during a drought period. White-winged chough groups showed similar significant genetic differentiation among groups during both drought and nondrought periods. However, we found female-biased dispersal during abundant rainfall years, which contrasts with the previous study conducted during a drought. We also examined differences in genetic structure in the present study, between groups breeding in suburbs versus native woodlands, finding higher within-group relatedness in woodland birds. Dispersal was female biased in both suburban and woodland habitat but subadult females in suburban habitat were more likely to disperse than adult females. We suggest that higher mortality in chough populations (both during a drought and in suburban habitats) led to more breeding opportunities, resulting in higher dispersal, and reflecting lower group stability. Our study suggests ecological conditions are important drivers of social structure in a cooperatively breeding bird, which are likely to be impacted by environmental change, including climate and urbanization. Highlights: Chough groups show significant genetic variation in drought and nondrought years. In nondrought years, in both suburbs and woodland, dispersal is female biased. Among suburban females, subadults are more likely to disperse than adults. In drought years dispersal is not sex biased.